Influence of the oil phase on the wound healing activity of sea cucumber extract-based cream formulations - Thiviya Sunmugam,; Hanisah Azhari,; Ng, Shiow Fern; Fazren Azmi, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Sea cucumbers are attractive marine natural sources as they are enriched with functional biomaterials that can contribute in accelerating wound healing. The present study was carried out to prepare cream formulations comprising extract of sea cucumber with different type of oil phase, namely F1 (olive oil), F2 (tea tree oil) and F3 (lemongrass oil) to assess the influence of the oil on the physicochemical properties and the wound healing efficacy of the creams. The formulated creams showed satisfactory physicochemical characteristics such as homogeneity, spreadability, rheology, pH, and showed no evidence of phase separation even when the creams were kept at extreme conditions. The ex vivo release profile of sea cucumber extract from the formulated creams was determined by using a Franz diffusion cells. F3 demonstrated a constant and yield the highest release percentage of sea cucumber extract, followed by F2 and F1. Topical application of the formulated creams on the excision wound in rats showed a significant wound healing efficacy compared to the control group. Among the creams formulation, F1 demonstrated a significantly higher rate of wound closure compared to F2, F3, and positive control. The wound healing efficacy of the formulated creams were not dependent on the ability of the oils in promoting skin permeation for the release of sea cucumber extract. This study depicted that lemongrass oil acted as a good skin permeation enhancer for the release of sea cucumber extract while olive oil worked in a more synergistic manner with sea cucumber extract in promoting wound healing.